Pengaruh Laba Bersih dan Arus Kas Operasi Terhadap Harga Saham Pada PT. Alam Sutera Realty Tbk - Khairunnisyah Khairunnisyah; Huda, Nurul; Wulandari Wulandari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to determine the simultaneous influence of net profit and operating cash flow on shares in PT. Alam Sutera Reality Tbk. This study is included in the category of population associative research in the study reveals that the sample is part of the number and characteristics possessed by the population.  The sample in this study is the financial statements of PT. Alam Sutera Realty Tbk for 10 years, from 2014 to 2023. The sampling technique used in this study is purposive sampling. states that purposive sampling is a technique for determining samples with certain considerations. With the criteria of financial statements available for 10 consecutive years, namely 2014-2023. The 10-year sample data already represents the existing population data for research needs. Data collection techniques Documentation, Literature Study. The data analysis technique used the Classical Assumption Test, Normality Test, Multicollinearity Test, Heterokedasticity Test, Autocorrelation Test, Multiple Linear Regression Analysis, Determination Coefficient Test and Correlation Coefficient. Then processed using SPSS, the results of the study showed that Net Profit and Operating Cash Flow had a simultaneous effect on the share price of Pt Alam Sutera Realty Tbk.